Ovarian Mucinous Cystadenoma Presenting as Pseudo-Meigs Syndrome - Shahiduzzaman, Gazi Khan Md; Chowdhury, Poritosh Kumar; Paik, Bishnupada; Biswas, Sankar Proshad; Islam, Rafiqul (Journal of Medicine, 2012)
Meigs syndrome is defined as the co-existence of benign ovarian tumor with ascites and hydrothorax that resolves after resection of tumor. The ovarian tumor in Meigs syndrome is fibroma. On the contrary, Pseudo- Meigs syndrome is characterized by the co-existence of hydrothorax, ascites and ovarian tumor either benign or malignant other than ovarian fibroma. The case herein concerns a 70 year old postmenopausal woman presented with the complaints of progressive shortness of breath on exertion and progressive swelling of lower abdomen. Her clinical and radiological examination revealed a massive right sided pleural effusion, mild ascites and a large heterogeneous pelvic mass with solid and cystic components, suggestive of left ovarian tumor. The patient underwent an exploratory laparotomy with excision of tumor, right ovary and whole of the uterus. The tumor was diagnosed histologically as an ovarian mucinous ystadenoma. Postoperative resolution of hydrothorax and ascites confirmed the diagnosis of Pseudo-Meigs syndrome. DOI: http://dx.doi.org/10.3329/jom.v13i2.12760 J Medicine 2012; 13 : 216-218